Generative AI in architectural designing and enhancing sheer ‎walls & slabs - Rasika Kachore , Mrs.; Jitendra Garud, MR.; Tiwari, Shubham; Shitole, Shriyash; Joshi, Krithik (International Journal of Advanced Mathematical Sciences, 2025)
The design of beam and slab systems of reinforced concrete shear wall structures has long been an ‎integral part of architectural and structural engineering. However, traditional methods applied to ‎these systems for design purposes are usually labor-intensive and inefficient if the complexities ‎encountered in modern buildings are considered. Generally, traditional methods heavily rely on time-‎consuming mathematical calculations and strict adherence to the design principles, which on a large ‎scale can lead to inaccuracy, delays, and increased costs. New demands on architectural design, ‎coupled with increasing concerns about sustainability, make even more innovative and adaptive ‎approaches necessary in the designing process.‎This paper addresses the shortcomings of the existing method by developing a new system that uses ‎generative artificial intelligence and deep learning for automated enhancement in the design of beam ‎and slab systems within shear wall structures. Through deep neural networks, high-dimensional ‎architectural data analysis with optimized structural layouts would be possible, which might realize ‎innovative design alternatives to meet the needs of buildings. This automation does not only diminish ‎the time and labor invested in the design process but also improves the designs overall accuracy and ‎efficiency with a performance equal to those produced by competent engineers.‎Another significant characteristic of the proposed system is its capability to integrate several aspects ‎of building design through the merging of attributes of space and elements. Additional leverage in ‎the design process comes from the interactive tools of the system: through it, architects and engineers ‎can iteratively experiment with design variations in real-time running, ensuring that their final ‎solution meets the aesthetic and functional demands of the project.‎The system further contains an environmental impact module, prioritizing sustainability in the design ‎process. Such a module evaluates the carbon footprint of any material or construction method in use, ‎ensuring, as much as possible, the use of environment-friendly materials. Since environmental ‎considerations are integrated into the system right from the outset, it vies for sustainable construction ‎practices, according to today's demand for green building solutions in the current construction ‎scenario‎.